RNase H2-Dependent Polymerase Chain Reaction and Elimination of Confounders in Sample Collection, Storage, and Analysis Strengthen Evidence That microRNAs in Bovine Milk Are Bioavailable in Humans. Issue 1 (25th January 2018) - Wang, Lanfang; Sadri, Mahrou; Giraud, David; Zempleni, Janos
Abstract: Background: Evidence suggests that dietary microRNAs (miRs) are bioavailable and regulate gene expression across species boundaries. Concerns were raised that the detection of dietary miRs in plasma might have been due to sample contamination or lack of assay specificity. Objectives: The objectives of this study were to assess potential confounders of plasma miR analysis and to detect miRs from bovine milk in human plasma. Methods: Potential confounders of plasma miR analysis (circadian rhythm, sample collection and storage, calibration, and erythrocyte hemolysis) were assessed by quantitative reverse transcriptase polymerase chain reaction (PCR) by using blood from healthy adults (7 men, 6 women; aged 23–57 y). Bovine miRs were analyzed by RNase H2–dependent PCR (rhPCR) in plasma collected from a subcohort of 11 participants before and 6 h after consumption of 1.0 L of 1%-fat bovine milk. Results: The use of heparin tubes for blood collection resulted in a complete loss of miRs. Circadian variations did not affect the concentrations of 8 select miRs. Erythrocyte hemolysis caused artifacts for some miRs if plasma absorbance at 414 nm was >0.300. The stability of plasma miRs depended greatly on the matrix in which the miRs were stored and whether the plasma was frozen before analysis. Purified miR-16, miR-200c, and cel -miR-39 were stable for ≤24 h at room temperature, whereas losses equaled ≤80% if plasma was frozen, thawed, and stored at room temperature for as little as 4 h. rhPCR distinguished between bovine and human miRs with small variations in the nucleotide sequence; plasma concentrations of Bos taurus ( bta )-miR-21-5p and bta -miR-30a-5p were >100% higher 6 h after milk consumption than before milk consumption. Conclusions: Confounders in plasma miR analysis include the use of heparin tubes, erythrocyte hemolysis, and storage of thawed plasma at room temperature. rhPCR is a useful tool to detect dietary miRs.